On the validity of the radiographic method for determining age of ancient salmon. (April 2017) - Hofkamp, Anthony R.; Butler, Virginia L.
Abstract: White rings visible on the centrum face of salmon vertebrae with X-rays have been used since the 1980s to age Pacific salmon ( Oncorhynchus spp.), which in turn have been used to determine salmon species, season of capture and season of site occupation. This approach relies on a variety of assumptions, the most fundamental of which is that rings represent true years. Recent aDNA analysis has shown that the X-ray approach has flaws but the source of the error has been unknown. Given the value of reconstructing salmon population demographics and life history from ancient remains, establishing a valid and reliable method of ageing salmon vertebrae is extremely worthwhile. The main goal of our study was to evaluate if X-ray images of ring patterns on vertebrae provide a valid method of estimating fish age. Vertebrae from 66 adult Chinook salmon ( O . tshawytscha ) of known age were studied with X-rays, thin sections or low-powered (10–30 ×) magnification. We found that the white bands observed in X-rays are structural walls that do not grow annually. While X-rays are not a valid method for ageing salmonids, incremental growth seen on the surface of fish centra shows great promise for reconstructing ancient fish life history. Highlights: Our goal was to evaluate whether X-ray images of ring patterns on salmonid vertebrae can be used to estimate fish age. Modern Chinook salmon vertebrae of known age were studied with X-rays, thin sections and low-powered magnification. White bands seen in X-rays are structural walls that do not grow annually. Incremental growth seen on the surface of fish centra show promise for reconstructing ancient fish life history.